2023
DOI: 10.1186/s13062-023-00363-z
|View full text |Cite
|
Sign up to set email alerts
|

Long-term administration of Western diet induced metabolic syndrome in mice and causes cardiac microvascular dysfunction, cardiomyocyte mitochondrial damage, and cardiac remodeling involving caveolae and caveolin-1 expression

Abstract: Background Long-term consumption of an excessive fat and sucrose diet (Western diet, WD) has been considered a risk factor for metabolic syndrome (MS) and cardiovascular disease. Caveolae and caveolin-1 (CAV-1) proteins are involved in lipid transport and metabolism. However, studies investigating CAV-1 expression, cardiac remodeling, and dysfunction caused by MS, are limited. This study aimed to investigate the correlation between the expression of CAV-1 and abnormal lipid accumulation in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Additionally, it has been noted that the expression of MFN2 in the hearts of MS mice is significantly decreased compared to the control group. Altogether, these data suggest that obesity can disrupt communication between the ER and mitochondria ( 41 ). Furthermore, it has been reported that the deletion of FUNDC1 aggravates cardiac remodeling, mitochondrial dysfunction, and cell death in high-fat diet (HFD)-fed mice.…”
Section: Role Of Mam In Cardiac Diseasementioning
confidence: 94%
See 1 more Smart Citation
“…Additionally, it has been noted that the expression of MFN2 in the hearts of MS mice is significantly decreased compared to the control group. Altogether, these data suggest that obesity can disrupt communication between the ER and mitochondria ( 41 ). Furthermore, it has been reported that the deletion of FUNDC1 aggravates cardiac remodeling, mitochondrial dysfunction, and cell death in high-fat diet (HFD)-fed mice.…”
Section: Role Of Mam In Cardiac Diseasementioning
confidence: 94%
“…As obesity rates continue to rise, attention is increasingly focused on the associated myocardial injuries. Mice with metabolic syndrome (MS) induced by prolonged consumption of a Western diet often exhibit cardiac microvascular dysfunction, mitochondrial damage, and cardiac remodeling ( 41 ). The reshaping and deformation of mitochondria and the ER markedly reduce MAM size in MS mouse cardiomyocytes.…”
Section: Role Of Mam In Cardiac Diseasementioning
confidence: 99%
“…Additionally, long-term consumption of diets high in fat and sucrose may cause abnormal lipid accumulation in both endothelial and myocardial cells in individuals with metabolic syndrome due to induced CAV1 expression. Lipid accumulation and lipotoxicity may have an impact on the destruction of MAMs and mitochondrial remodeling in cardiomyocytes, which could potentially lead to cardiomyocyte apoptosis, cardiac dysfunction, and remodeling ( Liu et al, 2023 ).…”
Section: Mitochondria-associated Endoplasmic Reticulum Membranes Cont...mentioning
confidence: 99%
“…Regulation of vascular permeability is also dependent on VEGF receptors but proceeds via a separate signaling pathway, namely via AKT and/or SRC activation (Simons et al 2016). EC dysfunction in MetS has been linked to oxidative stress and metabolic deregulation of ECs, which in turn affect vascular tone, permeability, angiogenesis, and surface molecule expression, and may subsequently trigger leukocyte adhesion, inflammation, and EC death (Liu et al 2023).…”
Section: Introductionmentioning
confidence: 99%